Schwann cell-derived exosomes ameliorate peripheral neuropathy induced by ablation of dicer in Schwann cells - Wang, Lei; Lu, XueRong; Szalad, Alexandra; Liu, Xian Shuang; Zhang, Yi; Wang, Xinli; Golembieski, William Anthony; Powell, Brianna; Mccann, Mikkala; Lu, Mei; Chopp, Michael; Zhang, Zheng Gang (Frontiers in Cellular Neuroscience, 2024)
Background MicroRNAs (miRNAs) in Schwann cells (SCs) mediate peripheral nerve function. Ablating Dicer, a key gene in miRNA biogenesis, in SCs causes peripheral neuropathy. Exosomes from healthy SCs (SC-Exo) ameliorate diabetic peripheral neuropathy in part via miRNAs. Thus, using transgenic mice with conditional and inducible ablation of Dicer in proteolipid protein (PLP) expressing SCs (PLP-cKO), we examined whether SC-Exo could reduce peripheral neuropathy in PLP-cKO mice. Methods PLP-cKO mice at the age of 16 weeks (8 week post-Tamoxifen) were randomly treated with SC-Exo or saline weekly for 8 weeks. Age-and sex-matched wild-type (WT) littermates were used as controls. Peripheral neurological functions, sciatic nerve integrity, and myelination were analyzed. Quantitative RT-PCR and Western blot analyses were performed to examine miRNA and protein expression in sciatic nerve tissues, respectively. Results Compared to the WT mice, PLP-cKO mice exhibited a significant decrease in motor and sensory conduction velocities, thermal sensitivity, and motor coordination. PLP-cKO mice exhibited substantial demyelination and axonal damage of the sciatic nerve. Treatment of PLP-cKO mice with SC-Exo significantly ameliorated the peripheral neuropathy and sciatic nerve damage. PLP-cKO mice showed a substantial reduction in a set of Dicer-related miRNAs known to regulate myelination, axonal integrity, and inflammation such as miR-138, −146a and − 338 in the sciatic nerve. In addition, PLP-cKO mice exhibited significant reduction of myelin forming proteins, early growth response 2 (EGR2) and sex determining region Y-box10 (Sox10), but significantly increased myelination inhibitors, Notch1, c-Jun, and Sox2 and the axonal growth inhibitor phosphatase and tens in homolog (PTEN). However, SC-Exo treatment reversed the PLP-cKO altered miRNAs and proteins. Conclusion This study demonstrates that exogenous SC-Exo ameliorate peripheral neuropathy induced by Dicer ablation in PLP expressing SCs. The therapeutic benefit may be mediated by the SC-Exo altered miRNAs and their targeted genes.